2017
DOI: 10.1142/s0218127417500961
|View full text |Cite
|
Sign up to set email alerts
|

Observer-Pattern Modeling and Slow-Scale Bifurcation Analysis of Two-Stage Boost Inverters

Abstract: This paper deals with modeling and bifurcation analysis of two-stage Boost inverters. Since the effect of the nonlinear interactions between source-stage converter and load-stage inverter causes the “hidden” second-harmonic current at the input of the downstream H-bridge inverter, an observer-pattern modeling method is proposed by removing time variance originating from both fundamental frequency and hidden second harmonics in the derived averaged equations. Based on the proposed observer-pattern model, the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This time-variance is the main difficulty in stability analysis of the system. To eliminating the effect of time-variance, the system is transformed into a time-invariant one using an observer-pattern modeling method [21,22]. Notice that sin(ωt) and cos(ωt) only exist in the expressions of di o /dt and du c2 /dt.…”
Section: Observer-pattern Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This time-variance is the main difficulty in stability analysis of the system. To eliminating the effect of time-variance, the system is transformed into a time-invariant one using an observer-pattern modeling method [21,22]. Notice that sin(ωt) and cos(ωt) only exist in the expressions of di o /dt and du c2 /dt.…”
Section: Observer-pattern Modelmentioning
confidence: 99%
“…The main difficulty for this is that linearization process must be performed around a fixed steady-state operating point rather than a steady-state time-periodic trajectory [18]. To deal with this problem, an observer-pattern modeling method [21,22] is proposed that eliminates the effect of time-variance.…”
Section: Introductionmentioning
confidence: 99%
“…In [8][9][10][11], the essence of the slow-scale instability phenomenon in a voltage-source inverter is analyzed and the analytical expression of the oscillation frequency is derived. In [12,13], the fast-scale instability phenomenon in a voltage-source single-phase H-bridge inverter was studied, and the essence of this phenomenon was analyzed. These studies revealed the profound mechanism of nonlinear phenomena in H-bridge inverters.…”
Section: Introductionmentioning
confidence: 99%